Plunkett's artificial intelligence (AI) & machine learning industry almanac. the only comprehensive guide to the artificial intelligence & machine learning industry - Plunkett, Jack W. (Plunkett Research, Ltd., 2022)
A market research guide to the Artificial Intelligence (AI) and Machine Learning industry. Includes statistical tables, trends analysis, and profiles of leading companies in all facets of artificial intelligence, both public and private, U.S. and international. A complete overview, industry analysis and report in one superb, value-priced package.